Sifat maskulin dan tingkah laku membuli - Jamal Safri Saibon,; Faridah Karim,; Zuria Mahmud, (penerbit ukm, 2010)
This study aimed to investigate how masculinity influences bullying behaviors among male secondary students. Four hundred and twenty male students from five schools with high discipline problems in the Penang Island answered the Level of Bully Behavior Inventory (Inventori Tahap Tingkah Laku Buli). From this group, 74 students who scored high and medium were asked to answer the Students’ Masculine Level Inventory (Inventori Tahap Maskulin Pelajar) and were interviewed. Results showed significant correlation between the level of bullying behaviors and the level of masculinity. These male bullies described themselves most as humorous, organized, atheletics, and high spirited but least as macho looking, fast runner, strong body built, and rich. The interview revealed that these boys bullied so that they will be favoured by peers, liked by girls, and feared by other students. Implications of the study on the personality development of male students are discussed.